COMPORTAMENTO ELETROCINÉTICO EM ÁREAS IMPACTADAS POR ÍONS METÁLICOS - ESTUDOS EXPERIMENTAIS - Sumi, Ernesto; Hypolito, Raphael; Gamito, Daniela (Águas Subterrâneas, 2013)
Electrokinetic remediation is a technique to restore a contaminated area, which has not been used in large-scale in Brazil. It is based on the application of an electric current of low intensity between two electrodes or more through the soil. Among the soil particles there are water solutions (interstitials solutions), that become ionic with electric conductivity and have particular characteristics. Therefore, the passing of an electric current can mobilize and concentrate ionic types through the electromigration and electroosmosis phenomena to the electrodes. Such technique is used in many other fields, but its application is extended mainly to the remediation of groundwater and impacted clay soil which are crucial to this project. The present study has as main objectives the research and improvement of new electrokinetic techniques to the remediation of impacted groundwater and clay soil for already impacted tropical sites. Experimental studies will be conducted on laboratory stand with products of various types simulating different kinds of soil, and varying the experimental conditions (different composition electrodes, electric current, humidity, permeability, etc). The information presented in this article corresponds to preliminary study results; nonetheless, it will contribute to a better understanding of electrochemistry remediation process applied in contaminated sites real situation.